Outage Probability Analysis of Mixed RF-FSO System Influenced by Fisher-Snedecor Fading and Gamma-Gamma Atmospheric Turbulence - Petkovic, Milica I; Ivanis, Predrag N; Djordjevic, Goran T (arXiv.org, 2022)
In this paper, we investigate a dual-hop relaying system, composed of radio frequency (RF) and free-space optical (FSO) link. Decode-and-forward (DF) relay is employed to integrate the first RF link and the second line-of-sight FSO links. The RF channel is assumed to be subject to recently proposed Fisher-Snedecor fading model, which was shown to be convenient for modeling in realistic wireless communication scenarios. The FSO channel is affected by Gamma-Gamma distributed atmospheric turbulence. Expression for the outage probability is derived and utilized to present numerical results. Based on presented results, the effects of various RF and FSO channels parameters on the overall system performance are examined and discussed.